The Encyclopedia of Child and Adolescent Development 2020
DOI: 10.1002/9781119171492.wecad475
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Competence

Abstract: Emotional competence (EC) is a multifaceted construct encompassing a broad range of emotion‐related skills (e.g., perception) and dispositional qualities (e.g., self‐efficacy) that are considered important for psychological, social, and educational adjustment across adolescence. This entry describes how EC is defined and measured, together with developmental changes in EC across the adolescent period. Emotional intelligence theory offers a holistic framework for organizing EC research. Using that framework as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…La competencia emocional ha sido usada como término que alude a un constructo multidimensional que incluye una colección de habilidades emocionales (el conocimiento, la percepción o la expresión emocional), capacidades (la regulación cognitiva de las emociones) y cualidades disposicionales (la empatía o la autoefi cacia emocional) (Davis y Qualter, 2020). No obstante, aunque ha sido un término ampliamente usado, la competencia emocional carece de una teoría unifi cada que delimite de forma sistemática y consensuada cuáles son sus elementos constituyentes (Pérez-González et al, 2020).…”
Section: Competencia Emocional Docenteunclassified
“…La competencia emocional ha sido usada como término que alude a un constructo multidimensional que incluye una colección de habilidades emocionales (el conocimiento, la percepción o la expresión emocional), capacidades (la regulación cognitiva de las emociones) y cualidades disposicionales (la empatía o la autoefi cacia emocional) (Davis y Qualter, 2020). No obstante, aunque ha sido un término ampliamente usado, la competencia emocional carece de una teoría unifi cada que delimite de forma sistemática y consensuada cuáles son sus elementos constituyentes (Pérez-González et al, 2020).…”
Section: Competencia Emocional Docenteunclassified
“…Emotional Competence has been used as an umbrella term and as a multifaceted construct encompassing a collection of emotion-related skills (e.g., emotion knowledge, emotion perception emotion regulation), abilities, and dispositional qualities (e.g., emotional self-efficacy), that enable an individual to function effectively in emotion-laden situations (Davis and Qualter, 2020). While the concept, or at least the general idea, of Emotional Competence has occasionally been used in literature that is lacking a comprehensive theory or model, EI has attracted unprecedented scientific attention and publications over the last 30 years, and it has become the unifying framework for describing and assessing multiple components of Emotional Competence.…”
Section: Conceptual Clarificationmentioning
confidence: 99%
“…The EI literature has progressively led to "two primary research streams" (Barchard et al, 2016, p. 289), according to which EI can be conceptualized and measured in two distinct, albeit, complementary constructs (Petrides, 2001;Pérez et al, 2005;Stough et al, 2009;Keefer et al, 2018); (1) as a typical performance tested personality trait (Trait EI), representing behavioral dispositions and perceptions of emotion-related competencies (Pérez-González and Sanchez-Ruiz, 2014;Petrides K. V. et al, 2016); or (2) as a maximum performance construct, comprising a set of intellectual abilities for reasoning about emotion (Ability EI; Mayer et al, 2016). Taken together, these two approaches to EI correspond conceptually and operationally with many aspects of Emotional Competence (Davis and Qualter, 2020). Given that Trait EI is conceived as a personality trait and Ability EI as a type of intelligence, Alba-Juez and Pérez-González (2019) suggested that the former might be reinterpreted as the non-cognitive/automatic (temperamental) component of Emotional Competence while the latter might be interpreted as the cognitive/conscious component.…”
Section: Conceptual Clarificationmentioning
confidence: 99%
“…Dentro de esta variedad de modelos hay diferencias, pero también hay puntos en común en los que debe considerarse los componentes de la IE, resultando ser complementarios entre si (Ciarrochi et al, 2000;. Recientes revisiones de la literatura sugieren que la IE podría ser interpretada como el mejor indicador general de competencia emocional (Davis y Qualter, 2020;Pérez-González at al., 2020), dado que no existe un modelo comprehensivo de competencia emocional y, por tanto, ésta suele evaluarse a partir de distintas combinaciones alternativas de variables afectivas, como han discutido recientemente Martínez-Saura et al (2021).…”
Section: Introductionunclassified